The meant and functions of mind in the Principles of Sunni jurisprudence - Navid Naghshbandi (مطالعات تطبیقی فقه و اصول مذاهب)
An important and challenging issue from the beginning of the history of Ijtihad is the role of mind in the inference of religious judgments. Some scholars in the Sunni have been able to find a useful role for it, far from excessive and worthless among the advocates and opponents, the maximal and minimal role of mind in the process of inference and Use mind as a useful tool without putting up an independent part for it in their books and discussions. Different roles of mind cannot be denied in the inference and understanding of religious purposes and religious comparison, although it has never been given free decision-making. This research is conducted analytically using library resources to review the role of reason in ijtihad based on the principles of Sunni jurisprudence and the result is that the greatest role of mind is in identifying the main being and understanding the general goals of the religion and comparative works and the implementation of religious laws within the community.